Standardized studies of the oral microbiome: From technology‐driven to hypothesis‐driven. Issue 2 (11th April 2022) - Gao, Chuqi; Li, Xuantao; Zhao, Xiaole; Yang, Peiyue; Wang, Xiao; Chen, Xiaoli; Chen, Ning; Chen, Feng
Abstract: The microbiome is in a symbiotic relationship with the host. Among the microbial consortia in the human body, that in the oral cavity is complex. Instead of repeatedly confirming biomarkers of oral and systemic diseases, recent studies have focused on a unified clinical diagnostic standard in microbiology that reduces the heterogeneity caused by individual discrepancies. Research has also been conducted on other topics of greater clinical importance, including bacterial pathogenesis, and the effects of drugs and treatments. In this review, we divide existing research into technology‐driven and hypothesis‐driven, according to whether there is a clear research hypothesis. This classification allows the demonstration of shifts in the direction of oral microbiology research. Based on the shifts, we suggested that establishing clear hypotheses may be the solution to major research challenges. Abstract : Genomics technologies have undoubtedly boosted the process of oral microbiology research which broadens people's understanding of diseases. Studies driven by genomics technologies tend to obtain a microbiological portrait of a specific population and then describe it. However, the recent studies share some goals even more concrete and definite, which symbolizes a critical turning point of global trend naturally from technology‐driven to hypothesis‐driven. Hypothesis‐driven studies have currently focused on the validation of pathogenic mechanisms and the effectiveness evaluation of therapeutics. Highlights: Genomics technologies have undoubtedly boosted the process of oral microbiology research which broadens people's understanding of diseases. Studies driven by genomics technologies tend to obtain a microbiological portrait of a specific population and then describe it. However, the recent studies share some goals even more concrete and definite, which symbolizes a critical turning point of global trend naturally from technology‐driven to hypothesis‐driven. Hypothesis‐driven studies have currently focused on the validation of pathogenic mechanisms and the effectiveness evaluation of therapeutics.